Cointegration and Toda-Yamamoto Causality between Government Subsidies, Domestic Investment, and Economic Growth in Egypt - Moustafa, Marwa Mohamed Ali (The Arab Journal of Administration, 2024)
The research aims to analyze and measure the relationship between government subsidies, domestic investment, and economic growth, using annual time series data on Egypt during the period (1990-2022). based on Autoregressive Distributed Lag Model (ARDL) and bound test To investigate the existence of cointegration between the variables and the Toda- Yamamoto (TY) causality test to investigate the direction of the causal relationship between variables in the long run. The research concluded that there is a cointegration relationship between the variables of the study, where domestic investment had a positive and significant impact on economic growth in the short and long run, and the inflation rate had an inverse and significant impact on economic growth in the long run, but this impact was weak, while government subsidies had a positive impact on Economic growth, but it is insignificant. Regarding testing the causality of TY in the long run, there was a direct causal relationship in one direction from local investment to economic growth. The study also found that there is a bidirectional causal relationship between domestic investment and government support, which confirms the importance of programs of subsidies to various productive sectors and the subsidies to Industrial zones and export provided by the Egyptian government and their role in increasing domestic investment. The study also found a direct causal relationship from inflation to domestic investment. The study recommends that government subsidies is very important in particular the subsidies to economic activities that would positively impact on domestic investment and thus economic growth.